Synthesizing Iron Atom Doped Carbon Nanotubes - Kutelia, Elguja R; Bakhtiyarova, Ayten S; Bakhtiyarov, Sayavur I (Media Mesin: Majalah Teknik Mesin, 2025)
One of the main challenges in synthesizing polytetrafluoroethylene (PTFE)-based iron cluster-doped carbon nanotube (CNT) nanocomposites is achieving uniform doping without causing aggregation or phase separation of the iron clusters, which can adversely affect the material’s properties. Iron nanoparticles tend to agglomerate due to their strong magnetic interactions and high surface energy, resulting in inhomogeneous doping that diminishes the effectiveness of the composite in applications like electromagnetic shielding, catalysis, or energy storage. To mitigate this, controlled synthesis techniques such as Chemical Vapor Deposition (CVD) with regulated precursor flow rates or solution-based methods with surfactants can be utilized. Accurate characterization using SEM-EDX analysis is also crucial, although distinguishing iron clusters from the carbon matrix can be difficult due to similar contrast levels. Complementary techniques like transmission electron microscopy (TEM) or X-ray photoelectron spectroscopy (XPS) can provide more detailed structural insights.